2010
DOI: 10.1590/s0034-737x2010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e qualidade de figos Roxo de Valinhos submetidos à fertirrigação e ao armazenamento refrigerado

Abstract: Effect of fertigation and cold storage on yield and quality of 'Roxo de Valinhos' figsThe low productivity of figs in Brazil is usually associated with water and nutrition deficiency. The aim of this work was evaluate the effect of fertigation with doses of nitrogen and potassium on yield and quality of the 'Roxo de Valinhos' figs during cold storage. The field experiment was conducted during two years, and in the last year, the fruits were stored at 0.5° C for fifteen days. The treatments were a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Originating in the Middle East, it is well adapted to humid and temperate subtropical climates, which allows its cultivation in various regions, such as the southeast of Brazil (FRONZA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Originating in the Middle East, it is well adapted to humid and temperate subtropical climates, which allows its cultivation in various regions, such as the southeast of Brazil (FRONZA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Originally from the Middle East, it has adapted to the humid and temperate subtropical climate, and so can be grown in various regions of Brazil. Its fruit can be appreciated in natura or processed, but is considered fragile, as it has a short postharvest life, even when stored under refrigeration (DALASTRA et al, 2009;FRONZA et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Originária do Oriente Médio, ela apresenta adaptação ao clima subtropical úmido e temperado, por isso seu cultivo pode ocorrer em diversas regiões do Brasil. Seus frutos podem ser apreciados in natura ou processados, porém são considerados frágeis por apresentarem uma breve vida pós-colheita, mesmo armazenados sob refrigeração (DALASTRA et al, 2009;FRONZA et al, 2010).…”
unclassified
“…, Gonçalves et al (2006b),Leonel & Tecchio (2008) andFronza et al (2010), studying the fig fruit quality for different Brazilian regions, with maximum values of 13%. The climatic conditions (Figure 1) present in the region of the study can explain the higher SST observed in this study, generating high brightness, increasing photosynthetic capacity of the plants and better sugar translocation from the leaves to the fruit, being a relative sourcedrain.…”
mentioning
confidence: 99%